A study on the spatial construction strategies of ethnic minority villages based on compound ecosystem theory. Issue 1 (June 2020) - Shao, Dandan; Han, Rong
Abstract: This article selects minority villages as the research object. The socio-economic-natural complex ecosystem theory is applied to the spatial construction of ethnic minority villages, and the landscape ecology and ecological aesthetics are combined to study the landscape planning of ethnic villages. Based on the rural realities, the problems, structures, features, and functions in the landscape planning of ethnic villages are analyzed from three levels: the natural ecological subsystem, the economic ecological subsystem, and the social ecological subsystem. The guiding thoughts, principles, and methods of the landscape planning of ethnic villages are put forward, and the relationship between the spatial planning of ethnic villages and the shaping of ethnic characteristics is summarized through the interpretation of related concepts and the analysis of research status at home and abroad. Finally, a strategy for the spatial construction of ethnic villages was obtained with a view to providing theoretical basis and reference for future national village landscape planning.